2022
DOI: 10.3389/fcell.2022.829067
|View full text |Cite
|
Sign up to set email alerts
|

TFP5-Mediated CDK5 Activity Inhibition Improves Diabetic Nephropathy via NGF/Sirt1 Regulating Axis

Abstract: Diabetic nephropathy (DN) is one of the leading causes of chronic kidney disease (CKD), during which hyperglycemia is composed of the major force for the deterioration to end-stage renal disease (ESRD). However, the underlying mechanism triggering the effect of hyperglycemia on DN is not very clear and the clinically available drug for hyperglycemia-induced DN is in need of urgent development. Here, we found that high glucose (HG) increased the activity of cyclin-dependent kinase 5 (CDK5) dependent on P35/25 a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 56 publications
0
4
0
Order By: Relevance
“…CDK5's relevance extends beyond neurodegenerative diseases; for example, inhibiting its activity has shown promise in reducing facial inflammatory pain in mice (Hu et al, 2022). Investigating the CDK5–nerve growth factor/sirtuin 1 (NGF/SIRT‐1) regulatory axis pathway holds potential for the development of treatments for diabetic nephropathy (Cao et al, 2022). Furthermore, knockdown of CDK5 has been found to inhibit HIF‐1α expression (Chao et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…CDK5's relevance extends beyond neurodegenerative diseases; for example, inhibiting its activity has shown promise in reducing facial inflammatory pain in mice (Hu et al, 2022). Investigating the CDK5–nerve growth factor/sirtuin 1 (NGF/SIRT‐1) regulatory axis pathway holds potential for the development of treatments for diabetic nephropathy (Cao et al, 2022). Furthermore, knockdown of CDK5 has been found to inhibit HIF‐1α expression (Chao et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…We have previously confirmed that TFP5 can effectively inhibit CDK5/P25 activity, and can reduce apoptosis in neurodegeneration experiments and HG‐stimulated neurons experiment, without affecting the physiological activities of CDK5/P35 and other CDKs (Amin et al, 2016; Binukumar et al, 2014; Shukla et al, 2013). In addition, we found that TFP5 regulates the nerve growth factor/sirtuin 1 axis by inhibiting the hyperactivity of CDK5/P25 in a diabetic nephropathy model, inhibiting oxidative stress and reducing apoptosis (Cao et al, 2022). Therefore, we treated the diabetic model with TFP5 in the present study.…”
Section: Discussionmentioning
confidence: 99%
“…3 Patients with DN have increased proteinuria and decreased glomerular filtration rate. 4 Hyperglycemia is considered a main risk factor for DN. 5 Nonetheless, the potential mechanisms underlying the effects of hyperglycemia are not very unclear.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, it was estimated ~38.8% and 23% of ESRD cases were caused by DN in the United States and China, respectively 3 . Patients with DN have increased proteinuria and decreased glomerular filtration rate 4 . Hyperglycemia is considered a main risk factor for DN 5 .…”
Section: Introductionmentioning
confidence: 99%